If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-3x + -3) = 5x + -15 Reorder the terms: -5(-3 + -3x) = 5x + -15 (-3 * -5 + -3x * -5) = 5x + -15 (15 + 15x) = 5x + -15 Reorder the terms: 15 + 15x = -15 + 5x Solving 15 + 15x = -15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 15 + 15x + -5x = -15 + 5x + -5x Combine like terms: 15x + -5x = 10x 15 + 10x = -15 + 5x + -5x Combine like terms: 5x + -5x = 0 15 + 10x = -15 + 0 15 + 10x = -15 Add '-15' to each side of the equation. 15 + -15 + 10x = -15 + -15 Combine like terms: 15 + -15 = 0 0 + 10x = -15 + -15 10x = -15 + -15 Combine like terms: -15 + -15 = -30 10x = -30 Divide each side by '10'. x = -3 Simplifying x = -3
| -27=x+9 | | txy=56 | | ln(x)+ln(x+29)=ln(62) | | X+6=-5x+30 | | -36t^2+18t=0 | | x^2y(xy-u)= | | -5(-3x-3x)=5x-15 | | 2154.28*.08= | | 2(n+8)=-18 | | x*0.07=150.80 | | X-(3-4)-1=5x-9-x | | 5x-5=6+6x | | 1/6m=20 | | (x+5)(-4x-2)(2x-1)=x | | 23n+10m+2n=180 | | 6m(m+4)=5m-15 | | 6m=20 | | 2x9/3 | | 2x^6+23x-25=0 | | y=-1+.5x | | 0.3x-8.1=-3 | | 0.9n+5.87=5.19-1.1n | | -49+6x=-3x+68 | | -11c-4=15 | | 3-4i=-2x+8yi | | 25=5(r-7)-7(6+8r) | | -27+5x=29-2x | | 0.25t+30=59.50 | | 61=2x | | 4s-15=19 | | -11-4=15 | | 29=-9(4d+7) |